Multivariate outlier detection in currency exchange rate - Sharif, Shamshuritawati; Djauhari, Maman. A.; Yusoff, Nur Syahidah (IJENS Publisher, Rawalpindi, Pakistan, 2013)
In correlation networks analysis, the influential currencies is usually identified by using minimal spanning tree (MST) to filter the important information followed by the centrality measures analysis.In this paper, we introduce an analysis to identify the currencies that might have different behaviour compared to the others which is also conducted based on MST by using outlier labelling and testing.A case study on 78 currency exchange rate will be reported and discussed.